Gynaecological bacterial infections: the physical and psychosocial consequences and challenges of management in resource-limited settings - Adiri, Charles O.; Nwagha, Uchenna I.; Okeke, Tochukwu C.; Izuka, Emmanuel O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Gynecological bacterial infections (GBIs) are prevalent in our environment and as a result pose a number of physical, social and psychological consequences. These infections are acquired through several ways. Treating GBIs is a daunting task making its control the most important strategy to alleviating its physical and psychosocial consequences. To highlight the physical, social, and psychological consequences of gynaecological bacterial infections in our resource limited setting. To highlight the hugely unresolved challenges associated with the management of gynecological bacterial infections in our resource-limited setting. Several databases (Medline, Google Scholar, Pubmed, WHO’s Hinari and Wikipedia) and some selected websites were searched using the following keywords: gynecological infections, vaginal infections and discharges, vaginal flora, sexually transmitted infections, pelvic inflammatory disease, syndromic management and challenges, psychosocial consequences, alternative medicine. A total of 5470 relevant articles were obtained between 1947 and 2018. Out of these only 256 relevant articles on the topic were reviewed. However, 213 were dropped for having an incomplete submission. Forty-three (43) articles were fully accessed and referenced. The high prevalence of GBIs poses a lot of burden on the reproductive and socio-economic lives of our women. This should be matched by behavioral changes, prompt diagnosis and early treatment; facilitated by accessible and affordable health care through improved government funding.